Nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst as well as preparation method and application thereof

Through the defect engineering of nickel-cobalt Prussian Blue-ZnIn2S4 core-shell photocatalyst and the S-type heterojunction design, the problem of limited light absorption range and low carrier separation efficiency of the photocatalyst is solved, and high-efficiency photocatalytic hydrogen production and stability improvement are achieved.

CN120325323APending Publication Date: 2025-07-18JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510483855.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The existing photocatalysts have limited light absorption range, low photogenerated carrier separation efficiency and high carrier recombination rate, which limit their practical application in photocatalytic hydrogen production. In addition, traditional Prussian blue analog materials have low charge separation efficiency and carrier trap effects.

Method used

The nickel-cobalt Prussian Blue-ZnIn2S4 core-shell photocatalyst is used to regulate the electronic structure of nickel-cobalt Prussian Blue analogue through defect engineering, and form an S-shaped heterojunction with ZnIn2S4 to construct a local surface plasmon resonance effect, broaden the light absorption range and promote the separation and transmission of photogenerated carriers.

Benefits of technology

The photocatalytic hydrogen production efficiency is significantly improved, the stability and photothermal synergy of the catalyst are enhanced, and the hydrogen production rate reaches 38.3mmol h-1g-1, with excellent chemical and thermal stability and good cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120325323A_ABST
    Figure CN120325323A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst as well as a preparation method and application thereof. According to the catalyst material, a nickel-cobalt Prussian blue analogue is used as an inner core, and is coated with a nanoflower-shaped ZnIn2S4 shell, so that a photocatalytic composite material with an S-shaped heterojunction structure is formed; the preparation method of the photocatalyst is simple, and the photocatalyst can be prepared through a low-temperature hydrothermal method; according to the catalyst, [Co (CN) 6] < 3-> defect regulation and a localized surface plasmon resonance effect are combined, an S-type heterojunction is constructed, an electronic structure is optimized, carrier migration is enhanced, the light absorption range is widened, and meanwhile the photo-thermal effect is utilized, so that the photocatalytic efficiency is remarkably improved; under the condition of simulating sunlight irradiation, the highest catalytic hydrogen production activity of the nickel-cobalt Prussian blue-ZnIn2S4 photocatalyst can reach 38.3 mmol h <-1 > g <-1 >, meanwhile, excellent stability is kept, and a new technical direction is provided for development of efficient photocatalytic hydrogen production materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photocatalyst, in particular to a nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst, and also relates to a preparation method and an application of the above photocatalyst. Background Art

[0002] Given the intensifying current energy crisis and the increasingly serious environmental pollution problems, the development of renewable energy has become an important task for global sustainable development. Among various energy forms, hydrogen is considered an ideal choice to solve the energy crisis and environmental problems due to its high energy density and pollution-free characteristics. Photocatalytic hydrogen production technology uses solar energy to drive water decomposition to produce hydrogen, which has the advantages of being clean, environmentally friendly and sustainable, and thus has become a research hotspot. However, most current photocatalysts have problems such as limited light absorption range, low separation efficiency of photo-generated carriers and high carrier recombination rate, which severely limit their practical applications. To improve photocatalytic performance, researchers have proposed using the photothermal effect of near-infrared light energy as an auxiliary strategy. The local surface plasmon resonance effect has received extensive attention because it can significantly enhance light absorption and extend the response range to the near-infrared region. However, the currently commonly used plasmonic metal materials mainly rely on scarce and expensive noble metals such as gold and silver, which limits their large-scale applications. Therefore, the development of non-precious metal-based photothermal materials has become the research focus.

[0003] Among numerous non-precious metal materials, Prussian blue analogs (PBAs) have attracted much attention due to their adjustable composition and structure, good near-infrared response and strong local surface plasmon resonance effect. Although the local surface plasmon resonance effect can be optimized by means of adjusting the structure, size and carrier concentration, etc., traditional Prussian blue analog materials still have problems such as low charge separation efficiency and carrier trapping effect, which affect their photocatalytic performance. In recent years, defect engineering, as an effective strategy, can enhance the separation efficiency of photo-generated carriers by adjusting the internal electronic structure of materials, thereby significantly improving photocatalytic activity. Therefore, it is of great research significance to develop Prussian blue analog materials based on defect regulation to achieve efficient photocatalytic hydrogen production with photo-thermal synergistic enhancement. Summary of the Invention

[0004] Object of the Invention: The object of the present invention is to provide a nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst with excellent photocatalytic hydrogen production performance and activity, and also provide a preparation method of the above photocatalyst and its application in efficient hydrogen production by water splitting.

[0005] Technical solution: The present invention discloses a nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst. The photocatalyst is a core-shell type S-scheme heterojunction photocatalyst, with a nickel-cobalt Prussian blue analogue as the core, and a nano-flower-like ZnIn2S4 shell is formed on the core surface from a Zn source, an In source, and an S source to achieve uniform coating of ZnIn2S4 and improve the photocatalytic performance.

[0006] Among them, the mass ratio of the nickel-cobalt Prussian blue analogue to ZnIn2S4 is 0.15-0.25:1, and further preferably 0.20:1; the layer thickness of the ZnIn2S4 nanosheets is about 5-10 nm.

[0007] The preparation method of the above nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst includes the following steps:

[0008] (1) Dissolve Ni(NO3)2·6H2O and C6H5Na3O7 in deionized water, stir, and then slowly pour it into a solution containing K3[Co(CN)6] for aging, centrifuge, wash, dry, and grind to obtain a blue nickel-cobalt Prussian blue analogue;

[0009] (2) Dissolve the Zn source, In source, and S source in a mixed solution of water and glycerol, stir, add the nickel-cobalt Prussian blue analogue prepared in step (1) to the above solution, carry out a water bath reaction, centrifuge, wash, dry, and grind to obtain a light green nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst.

[0010] Among them, in step (1), the concentration of Ni(NO3)2·6H2O is 0.028-0.032 mol / L, the concentration of K3[Co(CN)6] is 0.018-0.022 mol / L, and the concentration of C6H5Na3O7 is 0-0.047 mol / L, preferably 0, 0.013-0.017, 0.028-0.032, or 0.043-0.047 mol / L.

[0011] Among them, in step (1), the stirring time is 0.5-0.6 h, the aging time is 11.5-12.5 h, the aging temperature is room temperature, the washing and centrifugation speed is 8000-9000 r / min, the drying time is 7.5-8.5 h, and the drying temperature is 55-65 °C.

[0012] Among them, in step (2), the Zn source, In source, and S source are ZnCl2, InCl3·4H2O, and TAA respectively, and the mass ratio is 9-10:4-5:5-6.

[0013] Among them, in step (2), the concentration of ZnCl2 is 0.004 - 0.006 mol / L, the concentration of InCl3·4H2O is 0.004 - 0.006 mol / L, the concentration of TAA is 0.009 - 0.011 mol / L, and the volume ratio of water to glycerol is 14 - 15:3 - 4.

[0014] Among them, in step (2), the stirring time is 0.5 - 0.6 h, for the hydrothermal reaction, the heat preservation temperature is 75 - 85 °C, the heat preservation time is 1.5 - 2.5 h, and the washing and centrifugation speed is 8000 - 9000 r / min.

[0015] The above nickel - cobalt Prussian blue - ZnIn2S4 core - shell photocatalyst can also be applied to efficient hydrogen production by photocatalytic water splitting.

[0016] Principle of the invention: For the nickel - cobalt Prussian blue - ZnIn2S4 core - shell photocatalyst of the present invention, a nickel - cobalt Prussian blue analogue is used as the core material, and ZnIn2S4 is used as the outer shell layer. Through defect engineering regulation and S - type heterostructure construction, a large specific surface area is obtained. First, nickel - cobalt Prussian blue analogues with different defect numbers are prepared by the coprecipitation method. By adjusting the dosage of trisodium citrate, [Co(CN)6] 3- defects are effectively introduced to obtain nickel - cobalt Prussian blue analogue materials with different degrees of structural defects. Subsequently, the synthesized nickel - cobalt Prussian blue analogue samples are dispersed in a mixed solution composed of deionized water and glycerol, and then reaction sources such as ZnCl2, InCl3·4H2O, and thioacetamide are added. ZnIn2S4 nanosheets are uniformly grown under the condition of an 80 °C low - temperature water bath to form a nickel - cobalt Prussian blue - ZnIn2S4 core - shell photocatalyst with a core - shell structure.

[0017] For the nickel - cobalt Prussian blue - ZnIn2S4 core - shell photocatalyst of the present invention, the nickel - cobalt Prussian blue analogue has abundant surface active sites and defect structures, which can effectively adsorb Zn and In ions in the solution. Subsequently, thioacetamide is introduced as the S source to promote the reaction of the adsorbed metal ions with the S source on the core surface, forming ZnIn2S4 nanosheets with a nanoflower - like structure. This nanostructure can effectively avoid agglomeration phenomena and make full use of each active site on the surface of the core material, thereby achieving uniform and complete outer shell coverage. The prepared composite material has abundant defect structures and strong local surface plasmon resonance effects. The introduction of an appropriate amount of [Co(CN)6] 3- defects in the nickel - cobalt Prussian blue analogue material effectively regulates the electronic structure, improves the separation and transport efficiency of photo - generated carriers. At the same time, the local surface plasmon resonance effect significantly broadens the light absorption range, especially showing excellent photothermal response ability in the near - infrared region, thereby effectively increasing the temperature of the photocatalytic reaction, reducing the reaction energy barrier for photocatalytic hydrogen production, and promoting the reaction kinetic process.

[0018] In terms of the properties of composite materials, ZnIn2S4 has excellent light absorption ability, but its utilization rate of near-infrared light is relatively low. The introduction of nickel-cobalt Prussian blue analogue core materials significantly broadens the light absorption range to the near-infrared region. Its appropriate defect structure and local surface plasmon resonance effect can generate a strong photothermal effect under sunlight irradiation, increasing the overall temperature of the photocatalytic system, promoting the migration and separation of photo-generated carriers, and thus significantly improving the efficiency of photocatalytic hydrogen production. In addition, the S-type heterojunction formed between the nickel-cobalt Prussian blue analogue and ZnIn2S4 can effectively promote the rapid separation and transfer of photo-generated electron-hole pairs and maintain strong redox ability, thereby achieving efficient photocatalytic hydrogen production. The advantage of the nickel-cobalt Prussian blue-ZnIn2S4 core-shell structure is that it significantly broadens the light absorption range and enhances the photothermal effect through the defect structure and local surface plasmon resonance effect of the nickel-cobalt Prussian blue analogue core, while providing more active sites, preventing agglomeration, and forming an S-type heterojunction that effectively promotes the separation and transfer of photo-generated electron-hole pairs, thus significantly improving the photocatalytic hydrogen production efficiency and enhancing the stability of the catalyst.

[0019] Therefore, the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst of the present invention has a larger specific surface area and a wider light absorption range, and can significantly enhance the light absorption and utilization efficiency. The nickel-cobalt Prussian blue analogue core introduces abundant 3- defects through defect engineering, generating a strong local surface plasmon resonance effect and effectively broadening the light response range to the near-infrared region. The loading of ZnIn2S4 nanosheets further expands the light absorption region, effectively promotes the generation and separation of photo-generated electrons and holes, enhances the activity of photocatalytic hydrogen production, and significantly improves the photocatalytic reaction efficiency;

[0020] The nickel-cobalt Prussian blue-ZnIn2S4 core-shell structure exhibits excellent chemical stability and thermal stability, and can effectively resist corrosion and thermal decomposition during the process of photothermal synergistic photocatalysis. The nickel-cobalt Prussian blue analogue core material has good structural stability and can provide abundant electron transport channels, while the tightly coated structure formed by the outer ZnIn2S4 nanosheets effectively inhibits the agglomeration and structural degradation of the catalyst during the reaction process, thus ensuring the stability of the catalyst during long-term cyclic use;

[0021] The synergistic effect of defect regulation and S-type heterojunction significantly promotes the efficient separation and migration of photo-generated carriers. In the nickel-cobalt Prussian blue-ZnIn2S4 core-shell heterostructure, the built-in electric field and band bending effect effectively inhibit the recombination of photo-generated electrons and holes. The local surface plasmon resonance effect induced by defect engineering further enhances the photothermal effect, raises the system temperature, reduces the reaction energy barrier for photocatalytic hydrogen production, significantly accelerates the transport rate of photo-generated carriers, and thus increases the photocatalytic hydrogen production yield and reaction rate;

[0022] The nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst exhibits excellent photothermal conversion performance. The defect-rich nickel-cobalt Prussian blue analogue core can effectively absorb near-infrared light and convert it into heat energy, significantly increasing the reaction system temperature during the photocatalytic process, enhancing the photothermal coupling effect, and further promoting the mass transfer and reaction kinetics of reactant molecules. The layered structure of ZnIn2S4 nanosheets can effectively prevent heat dissipation and maintain the temperature stability of the reaction system, thereby improving the overall efficiency of photocatalytic hydrogen production;

[0023] Moreover, the photocatalyst of the present invention has excellent cycle stability and reusability. During the long-term photocatalytic cycle process, the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst maintains good structural stability and catalytic activity. The stable core-shell structure formed by the core structure of the nickel-cobalt Prussian blue analogue combined with the ZnIn2S4 shell effectively prevents the structural collapse or agglomeration of the material during the long-term reaction, thereby extending the service life of the catalyst and ensuring the lasting stability of the photocatalytic performance; under irradiation, the photo-generated electrons on the CB of the nickel-cobalt Prussian blue analogue spontaneously cooperate with the holes on the VB of ZIS under the action of IEF and band bending, resulting in S-type charge transfer behavior; [Co(CN)6] 3- The defect engineering of can regulate the electronic structure of NCPBA-Ds, promote the interfacial charge transfer from NCPBA-Ds to ZIS, and reduce the potential barrier for photocatalytic H2 generation reaction.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following remarkable advantages: (1) The nickel-cobalt Prussian blue analogue@ZnIn2S4 core-shell photocatalyst of the present invention has a larger specific surface area (32.67 m 2 g -1 ), and the light absorption range is broadened from the visible light region to the near-infrared light region; and it has excellent chemical stability and thermal stability, and can effectively resist corrosion and thermal decomposition during the photothermal synergistic photocatalytic process; (2) When applied to photocatalytic hydrogen production, the highest yield can reach 38.3 mmol h - 1 g -1, which is 23.4 times that of traditional ZnIn2S4; and it exhibits excellent photothermal conversion performance, with a photothermal conversion efficiency reaching 90.1%. Description of the Drawings

[0025] Figure 1 For the morphological study of the products prepared in the examples and comparative examples, where (a), (b), (c), and (d) are the scanning electron microscope (SEM) images of NCPBA-Ds-0, NCPBA-Ds-3, NCPBA-D-6, and NCPBA-Ds-9 respectively, and (e) and (f) are the transmission electron microscope (TEM) image and high-resolution transmission electron microscope (HRTEM) image of nickel cobalt prussian blue analogue @ZnIn2S4 respectively;

[0026] Figure 2 Element distribution image of the photocatalyst of the present invention;

[0027] Figure 3 Raman spectrum (a), Fourier transform infrared spectrum (b), N2 adsorption-desorption isotherm (c), pore size distribution (d), XPS measurement spectrum (e), and high-resolution XPS spectrum of Ni 2p (f) of nickel cobalt prussian blue analogue: (g) Co 1s, (h) C 1s, and (i) N 1s;

[0028] Figure 4 Electron spin resonance spectrum of nickel cobalt prussian blue analogue;

[0029] Figure 5 Ultraviolet-visible-near-infrared absorption spectrum (a), photothermal temperature change curve (b) of the powder material under AM1.5G irradiation, and infrared image (c) of nickel cobalt prussian blue analogue;

[0030] Figure 6 Photocatalytic hydrogen production performance diagram of the prepared samples;

[0031] Figure 7 Ultraviolet-visible-near-infrared absorption spectrum (a), photothermal temperature change curve (b) of the photocatalyst of the present invention and ZnIn2S4 under AM1.5G irradiation, photothermal conversion efficiency diagram (c), photocatalytic hydrogen production performance and hydrogen production rate diagrams (d) and (e) under AM 1.5G irradiation, and apparent quantum efficiency value (f);

[0032] Figure 8Among them, (a) Photothermal imaging diagram of the reaction solution of the photocatalyst of the present invention, (b) Photocatalytic hydrogen production performance diagram of the photocatalyst of the present invention at different temperatures, (c) Corresponding photocatalytic hydrogen production rate diagram, (d) Reaction activation energy of the photocatalyst of the present invention under different temperature conditions, (e) Transient photocurrent response curve of the photocatalyst of the present invention under different temperature conditions, (f) Electrochemical impedance spectroscopy diagram of the photocatalyst of the present invention at different temperatures, (g) Photoluminescence spectrum of the photocatalyst of the present invention under different temperature conditions;

[0033] Figure 9 Among them, (a) Band gap values of ZnIn2S4 and NCPBA-Ds-0, (b) Valence band X-ray photoelectron spectra of ZnIn2S4 and NCPBA-Ds-0, (c) Ultraviolet photoelectron spectra of ZnIn2S4 and NCPBA-Ds-0, (d) Schematic diagram of the relative energy band positions and S-type charge transfer mechanism between the original ZIS and NCPBA-Ds-0. Specific implementation mode

[0034] The technical solutions of the present invention will be further described below in conjunction with embodiments. The test materials used in the embodiments can be obtained through conventional channels.

[0035] Example 1

[0036] The preparation method of the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst of the present invention includes the following steps:

[0037] (1) Dissolve 0.6 mmol of Ni(NO3)2·6H2O completely in 20 mL of deionized water, and then slowly add 20 mL of 0.02 M K3[Co(CN)6] solution under stirring conditions. The obtained mixed solution is aged at room temperature for 12 h, and then the precipitate is collected by centrifugation and dried at 60 °C for 8 h, and ground to obtain a blue nickel-cobalt Prussian blue analogue;

[0038] (2) Dissolve 0.4 mmol of ZnCl2, 0.4 mmol of InCl3·4H2O and 0.8 mmol of TAA in a mixed solution of 64 mL of deionized water and 16 mL of glycerol, and stir for 0.5 h. Subsequently, add 40 mg of the pre-prepared blue nickel-cobalt Prussian blue analogue to the above solution and react in a water bath at 80 °C for 2 h. After the reaction is completed, the precipitate is collected by centrifugation and washed three times with ethanol to finally obtain the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst, denoted as NCPBA-Ds-0@ZIS-40.

[0039] Example 2

[0040] The nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst of the present invention, compared with Example 1, changes the addition amount of C6H5Na3O7, and its preparation method includes the following steps:

[0041] (1) Dissolve 0.6 mmol of Ni(NO3)2·6H2O and 0.3 mmol of C6H5Na3O7 completely in 20 mL of deionized water, and then slowly add 20 mL of 0.02 M K3[Co(CN)6] solution under stirring conditions. Age the obtained mixed solution at room temperature for 12 h, then collect the precipitate by centrifugation, dry it at 60 °C for 8 h, and grind to obtain a blue nickel-cobalt Prussian blue analogue;

[0042] (2) Dissolve 0.4 mmol of ZnCl2, 0.4 mmol of InCl3·4H2O, and 0.8 mmol of TAA in a mixed solution of 64 mL of deionized water and 16 mL of glycerol, and stir for 0.5 h. Subsequently, add 40 mg of the pre-prepared blue nickel-cobalt Prussian blue analogue to the above solution and react in a water bath at 80 °C for 2 h. After the reaction is completed, collect the precipitate by centrifugation and wash it three times with ethanol to finally obtain the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst, denoted as NCPBA-Ds-3@ZIS-40.

[0043] Example 3

[0044] The nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst of the present invention, compared with Example 1, changes the addition amount of C6H5Na3O7, and its preparation method includes the following steps:

[0045] (1) Dissolve 0.6 mmol of Ni(NO3)2·6H2O and 0.6 mmol of C6H5Na3O7 completely in 20 mL of deionized water, and then slowly add 20 mL of 0.02 M K3[Co(CN)6] solution under stirring conditions. Age the obtained mixed solution at room temperature for 12 h, then collect the precipitate by centrifugation, dry it at 60 °C for 8 h, and grind to obtain a blue nickel-cobalt Prussian blue analogue;

[0046] (2) Dissolve 0.4 mmol of ZnCl2, 0.4 mmol of InCl3·4H2O, and 0.8 mmol of TAA in a mixed solution of 64 mL of deionized water and 16 mL of glycerol, and stir for 0.5 h. Subsequently, add 40 mg of the pre-prepared blue nickel-cobalt Prussian blue analogue to the above solution and react in a water bath at 80 °C for 2 h. After the reaction is completed, collect the precipitate by centrifugation and wash it three times with ethanol to finally obtain the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst, denoted as NCPBA-Ds-6@ZIS-40.

[0047] Example 4

[0048] For the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst of the present invention, compared with Example 1, the addition amount of C6H5Na3O7 is changed, and its preparation method includes the following steps:

[0049] (1) Dissolve 0.6 mmol of Ni(NO3)2·6H2O and 0.9 mmol of C6H5Na3O7 completely in 20 mL of deionized water, and then slowly add 20 mL of 0.02 M K3[Co(CN)6] solution under stirring conditions. Age the obtained mixed solution at room temperature for 12 h, then collect the precipitate by centrifugation, dry it at 60 °C for 8 h, and grind it to obtain a blue nickel-cobalt Prussian blue analogue;

[0050] (2) Dissolve 0.4 mmol of ZnCl2, 0.4 mmol of InCl3·4H2O and 0.8 mmol of TAA in a mixed solution of 64 mL of deionized water and 16 mL of glycerol, and stir for 0.5 h. Subsequently, add 40 mg of the pre-prepared blue nickel-cobalt Prussian blue analogue to the above solution, and react in a water bath at 80 °C for 2 h. After the reaction is completed, collect the precipitate by centrifugation, and wash it three times with ethanol to finally obtain the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst, denoted as NCPBA-Ds-9@ZIS-40.

[0051] Comparative Example 1

[0052] The preparation method of nickel-cobalt Prussian blue analogue (NCPBA-Ds-0) includes the following steps:

[0053] (1) Dissolve 0.6 mmol of Ni(NO3)2·6H2O completely in 20 mL of deionized water, and then slowly add 20 mL of 0.02 M K3[Co(CN)6] solution under stirring conditions;

[0054] (2) Age the obtained mixed solution at room temperature for 12 h, then collect the precipitate by centrifugation, dry it at 60 °C for 8 h, and grind it to obtain a blue nickel-cobalt Prussian blue analogue, named NCPBA-Ds-0.

[0055] Comparative Example 2

[0056] The preparation method of nickel-cobalt Prussian blue analogue (NCPBA-Ds-3) includes the following steps:

[0057] (1) Dissolve 0.6 mmol of Ni(NO3)2·6H2O and 0.3 mmol of C6H5Na3O7 completely in 20 mL of deionized water, and then slowly add 20 mL of 0.02 M K3[Co(CN)6] solution under stirring conditions;

[0058] (2) The obtained mixed solution was aged at room temperature for 12 h, and then the precipitate was collected by centrifugation and dried at 60 °C for 8 h, and ground to obtain a blue nickel-cobalt prussian blue analogue, named NCPBA-Ds-3.

[0059] Comparative Example 3

[0060] Preparation method of nickel-cobalt prussian blue analogue (NCPBA-Ds-6), comprising the following steps:

[0061] (1) 0.6 mmol of Ni(NO3)2·6H2O and 0.6 mmol of C6H5Na3O7 were completely dissolved in 20 mL of deionized water, and then 20 mL of 0.02 M K3[Co(CN)6] solution was slowly added under stirring conditions;

[0062] (2) The obtained mixed solution was aged at room temperature for 12 h, and then the precipitate was collected by centrifugation and dried at 60 °C for 8 h, and ground to obtain a blue nickel-cobalt prussian blue analogue, named NCPBA-Ds-6.

[0063] Comparative Example 4

[0064] Preparation method of nickel-cobalt prussian blue analogue (NCPBA-Ds-9), comprising the following steps:

[0065] (1) 0.6 mmol of Ni(NO3)2·6H2O and 0.9 mmol of C6H5Na3O7 were completely dissolved in 20 mL of deionized water, and then 20 mL of 0.02 M K3[Co(CN)6] solution was slowly added under stirring conditions;

[0066] (2) The obtained mixed solution was aged at room temperature for 12 h, and then the precipitate was collected by centrifugation and dried at 60 °C for 8 h, and ground to obtain a blue nickel-cobalt prussian blue analogue, named NCPBA-Ds-9.

[0067] Comparative Example 5

[0068] Preparation method of ZnIn2S4, comprising the following steps:

[0069] (1) 272 mg of zinc chloride, 586 mg of indium chloride tetrahydrate and 300 mg of thioacetamide were dissolved in a mixture containing 8 ml of glycerol and 32 ml of H2O. The obtained mixture was stirred;

[0070] (2) The prepared solution was transferred to a water bath and heated with stirring at 80 °C for 2 h, and after the time ended, it was cooled to room temperature;

[0071] (3) The final product was washed three times with water and alcohol and dried in vacuo at 60 °C to obtain yellow ZnIn2S4.

[0072] As Figure 3 shown, Raman spectroscopy showed that there were two main absorption peaks at 2186 and 2203 cm -1 , corresponding to the vibration modes of the cyano ligands of the Co 3+ -C≡N-Ni 2+ coordination bond. In addition, it was observed that the peak intensity of -C≡N- in NCPBA-Ds-0 was the weakest, indicating the highest [Co(CN)6] 3- defect concentration in this sample. In the Fourier transform infrared spectrum, the absorption peaks at 473 and 2193 cm -1 were attributed to the bending vibration mode of Co-CN-Ni and the stretching vibration mode of C≡N, respectively, while the absorption peak near 3652 cm -1 was attributed to the absorption of water molecules in the O-H stretching vibration mode. As the amount of C6H5Na3O7 decreased, the intensity of the O-H vibration peak gradually increased, indicating a gradual increase in the ligand water content and a decrease in the crystallinity of the material. In addition, the N2 adsorption-desorption isotherm showed that the nickel-cobalt Prussian blue analogue samples presented an H3-type hysteresis loop of type IV isotherm, proving the existence of mesoporous structure in the materials. Further analysis gave specific surface areas of 35.67, 26.33, 19.49 and 13.82 m 2 g -1 , indicating that the disordered structure of the nickel-cobalt Prussian blue analogue gave it a large specific surface area. The pore size distribution curve showed that the nickel-cobalt Prussian blue analogue samples had larger pore sizes, indicating that the [Co(CN)6] 3- defects had a positive effect on the pore structure. X-ray photoelectron spectroscopy analysis further confirmed the chemical composition and elemental valence states of the nickel-cobalt Prussian blue analogue samples. The results showed that all samples contained Ni, Co, C and N elements. In the high-resolution XPS spectrum of Ni 2p, the peaks located at 875.2 and 873.8 eV corresponded to Ni2p 1 / 2 , the peaks at 856.2 and 857.6 eV corresponded to Ni 2p 3 / 2 , while the peaks at 880.5 and 862.9 eV were attributed to satellite peaks. As the number of defects increased, the main peak of Ni 2p shifted towards higher binding energy, the deconvoluted peaks related to Ni-N bonds (875.2 and 857.6 eV) gradually weakened, while the peaks related to Ni-O coordination (873.8 and 856.2 eV) increased. This indicated that due to the coordination deficiency of the -C≡N- ligands in the nickel-cobalt Prussian blue analogue, the oxidation state of Ni increased, thus facilitating charge transport kinetics. In the Co2p spectrum, Co 2p 1 / 2 and Co 2p 3 / 2can be unrolled into two peaks, indicating that Co in the nickel-cobalt Prussian blue analogue sample 2+ and Co 3+ coexist. The peaks at 796.7 and 781.4 eV correspond to the Co-N coordination bond, while the peaks at 794.4 and 776.7 eV are attributed to the Co 2+ -C bond. In all samples, the peak intensities and binding energies of Ni-O and Co 2+ in NCPBA-Ds-0 are the highest, indicating that it has the most [Co(CN)6] 3- defects. The high-resolution spectrum of C1s shows that the peaks at 288.3, 286.6, and 284.8 eV correspond to C=O, C≡N, and C-C bonds, respectively. The peaks in the N 1s spectrum are located at 399.8, 398.6, and 398.1 eV, corresponding to pyrrolic nitrogen, pyridinic nitrogen, and C≡N, respectively. The samples with stronger defect structures have lower C≡N peak intensities in the C1s and N1s spectra, and the diffraction peak of NCPBA-Ds-0 is the weakest, further proving that it has the largest number of defects. Combining the above characterization results, it can be seen that different amounts of C6H5Na3O7 as a chelating agent can effectively regulate the structural properties of the nickel-cobalt Prussian blue analogue, thereby realizing a unique low-defect framework structure. This structural property significantly promotes the effective separation and transport of photo-generated carriers, inhibits the rapid recombination of electron-hole pairs, and broadens the spectral absorption range, thus providing an effective guarantee for the improvement of photocatalytic performance.

[0073] As Figure 4 shown, all samples exhibit symmetric Lorentzian signals (g value = 2.004) under the corresponding magnetic fields, indicating the presence of [Co(CN)6] 3- defects in the lattice, and the signal of the NCPBA-Ds-0 sample is the strongest. From these data, it can be seen that as the content of the C6H5Na3O7 chelating agent decreases, the nickel-cobalt Prussian blue analogue samples show a more disordered morphology and a more chaotic crystal structure, which indicates that reducing the amount of C6H5Na3O7 can effectively reduce the crystallinity of the material and increase the number of structural defects.

[0074] As Figure 5As shown in the figure, the optical absorption wavelength of nickel-cobalt Prussian blue analogues was tested by ultraviolet-visible-near-infrared diffuse reflectance spectroscopy. All nickel-cobalt Prussian blue analogue samples showed strong light response, which was attributed to the local surface plasmon resonance effect of free carriers on the material surface. Among them, the NCPBA-Ds-0 sample showed the strongest absorption peak, which might be related to the enhanced ability of multiple refraction and reflection of light caused by its defect structure, thus improving the utilization rate of light energy. In addition, materials with excellent photothermal effects can be used as thermonuclear substrates to construct a photothermal-assisted photocatalytic system. The temperature changes on the surfaces of different nickel-cobalt Prussian blue analogues were tested by infrared thermal imaging and temperature change curves. Under simulated sunlight irradiation, different samples showed obvious temperature fluctuations within 0 - 120 s. The results showed that the surface temperature of NCPBA-Ds-0 increased most significantly, reaching 66.4 °C after 120 s of irradiation, followed by NCPBA-Ds-3 (57.1 °C), NCPBA-Ds-6 (54.7 °C), while the temperature of NCPBA-Ds-9 only rose to 51.1 °C, indicating that NCPBA-Ds-0 had a more significant photothermal effect. This result confirmed that the strong photothermal effect of the NCPBA-Ds-0 sample mainly depended on its enhanced light absorption ability, which could effectively increase the temperature of the photothermal-assisted photocatalytic system, thus promoting the migration of photogenerated carriers and the surface reaction kinetics, and significantly improving the photocatalytic activity.

[0075] As Figure 6 shown, the optimal theoretical mass ratio of nickel-cobalt Prussian blue analogues and ZnIn2S4 in the nickel-cobalt Prussian blue analogue@ZnIn2S4 heterojunction was studied. The NCPBA-Ds-0@ZIS-40 sample showed the best photocatalytic hydrogen production activity, reaching 76.6 mmol g -1 .

[0076] As Figure 7As shown, compared with pure ZnIn2S4, all nickel cobalt Prussian blue-ZnIn2S4 composite samples showed a significant enhancement in light absorption ability, and the absorption peak of ZnIn2S4 was extended to the near-infrared region under the action of the local surface plasmon resonance effect, thus effectively improving the utilization rate of sunlight. The color of the composite material is darker than that of ZnIn2S4, which is closely related to the enhancement of its light absorption ability. A strong light absorption ability is usually accompanied by a significant photothermal effect, and this phenomenon was verified by the temperature change of different nickel cobalt Prussian blue analog@ZnIn2S4 heterojunctions under illumination. After 120 s of illumination, the temperature of nickel cobalt Prussian blue analog@ZnIn2S4 can rapidly rise to 56.1 °C, which is significantly higher than that of other composite samples. This temperature rise is related to the defect-rich structure of nickel cobalt Prussian blue analog@ZnIn2S4, which can absorb more photons to generate photogenerated carriers, thus enhancing the photothermal effect. The internal photothermal conversion efficiency of nickel cobalt Prussian blue-ZnIn2S4 can reach 90.1%, further proving that its defect-rich structure endows excellent photothermal conversion ability. Nickel cobalt Prussian blue analog@ZnIn2S4 has the optimal photocatalytic hydrogen production performance, and the hydrogen production rate is 38.3 mmol h -1 g -1 , which is 23.4 times that of pure ZIS. In addition, the hydrogen production performance of all NCPBA-Ds-x@ZIS composite materials is better than that of pure ZnIn2S4, indicating that constructing an effective heterojunction can promote the transport of photogenerated carriers, inhibit the recombination of electron-hole pairs, and thus improve the photocatalytic hydrogen production activity. The apparent quantum efficiency of nickel cobalt Prussian blue analog@ZnIn2S4 at different wavelengths is highly matched with its light absorption characteristics, further proving its excellent photocatalytic activity in the full spectral region.

[0077] Such as Figure 8As shown, the infrared image indicates that the temperature of nickel-cobalt Prussian blue analogue @ZnIn2S4 can rise to 43.2 °C after 2 h, indicating that nickel-cobalt Prussian blue analogue @ZnIn2S4 has excellent photothermal effect. The temperature control experiment conducted by the circulating condensation system shows that with the increase of temperature, the photocatalytic hydrogen production performance of both ZnIn2S4 and nickel-cobalt Prussian blue analogue @ZnIn2S4 increases, while the photocatalytic activity of ZnIn2S4 is significantly less sensitive to temperature than that of nickel-cobalt Prussian blue analogue @ZnIn2S4, which proves that nickel-cobalt Prussian blue analogue @ZnIn2S4 can maintain a stable photothermal effect at different temperatures. According to the Arrhenius formula calculation, the reaction activation energies of ZnIn2S4 and nickel-cobalt Prussian blue analogue @ZnIn2S4 are 16.29 kJ / mol and 12.46 kJ / mol respectively. The lower activation energy barrier indicates that introducing nickel-cobalt Prussian blue analogue with excellent photothermal effect can significantly promote the hydrogen production process in the photocatalytic reaction system of nickel-cobalt Prussian blue analogue @ZnIn2S4. In addition, through photoelectrochemical experiment characterization, the behavior of photogenerated carriers in the photocatalytic reaction system of nickel-cobalt Prussian blue analogue @ZnIn2S4 at different temperatures was studied. With the increase of temperature, the photocurrent response curve of nickel-cobalt Prussian blue analogue @ZnIn2S4 increases, while the Nyquist plot of electrochemical impedance spectroscopy shows the opposite trend, indicating that higher temperature is conducive to the separation and transport of photogenerated electrons and reduces the recombination phenomenon during the carrier migration process. By testing the photoluminescence spectrum at different temperatures, it can be confirmed that the PL signal intensity of the nickel-cobalt Prussian blue analogue @ZnIn2S4 composite material decreases significantly with the increase of temperature, indicating that high temperature can effectively weaken the recombination of photogenerated electron-hole pairs.

[0078] As Figure 9 shown, the band gaps of ZnIn2S4 and NCPBA-Ds-0 obtained by Kubelka-Munk functional transformation are 2.49 and 2.72 eV respectively. The valence band values of ZnIn2S4 and NCPBA-Ds-0 obtained by valence band X-ray photoelectron spectroscopy are 1.45 and 2.04 eV respectively. By calculating the formula E VB-NHE = Φ + E VB-XPS –4.44, the E VB-NHE values of ZnIn2S4 and NCPBA-Ds-0 are obtained as 1.31 and 1.90 eV respectively. According to the formula E CB = E VB –E g, the calculated conduction band potentials of ZnIn2S4 and NCPBA-Ds-0 are -1.18 and -0.82 eV, respectively. Measured by ultraviolet photoelectron spectroscopy, the work functions of ZnIn2S4 and NCPBA-Ds-0 are 4.53 and 5.34 eV, respectively, further determining that the Fermi level of NCPBA-Ds-0 is lower than that of ZnIn2S4. The charge transfer mechanism of the energy band structures of ZIS and NCPBA-Ds-0 indicates that when the two semiconductor photocatalysts are in contact in the dark state, the free electrons of ZnIn2S4 can continuously migrate to NCPBA-Ds-0 until the Fermi levels are balanced. Due to the loss of electrons, the surface of ZIS is positively charged and the energy band bends upward, while the surface of NCPBA-Ds-0 is negatively charged and the energy band bends downward, resulting in the generation of an internal built-in electric field at the heterojunction interface. Under this condition, electrons and holes can only recombine at the interface and cannot flow in the reverse direction. Under illumination, the photo-generated electrons on the conduction band of NCPBA-Ds-0 and the holes on the valence band of ZnIn2S4 spontaneously cooperate under the action of IEF and energy band bending to form an S-type charge transfer behavior.

[0079] Therefore, the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst of the present invention has a larger specific surface area and a wider light absorption range, can significantly enhance the light absorption and utilization efficiency, has excellent chemical stability and thermal stability, can effectively resist corrosion and thermal decomposition during the photothermal synergistic photocatalysis process, and has excellent cycle stability and reusability. During the long-term photocatalytic cycle process, the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst maintains good structural stability and catalytic activity.

Claims

1. A nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst, characterized in that, The photocatalyst is a core-shell type S-scheme heterojunction photocatalyst with nickel-cobalt Prussian blue analogue as the core, and a nano-flower-shaped ZnIn2S4 shell is formed on the core surface by Zn source, In source and S source.

2. The photocatalyst according to claim 1, characterized in that, The mass ratio of the nickel-cobalt Prussian blue analogue to ZnIn2S4 is 0.15 - 0.25:

1.

3. A method for preparing the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst according to claim 1, characterized in that, It includes the following steps: (1) Dissolve Ni(NO3)2·6H2O and C6H5Na3O7 in deionized water, stir, and then slowly pour it into a solution containing K3[Co(CN)6] for aging, centrifugation, washing, drying, and grinding to obtain a blue nickel-cobalt Prussian blue analogue. (2) Dissolve Zn source, In source and S source in a mixed solution of water and glycerol, stir, add the nickel-cobalt Prussian blue analogue prepared in step (1) into the above solution, carry out a water bath reaction, centrifugation, washing, drying, and grinding to obtain a light green nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst.

4. The manufacturing method according to claim 3, characterized in that, In step (1), the concentration of Ni(NO3)2·6H2O is 0.028 - 0.032 mol / L, the concentration of K3[Co(CN)6] is 0.018 - 0.022 mol / L, and the concentration of C6H5Na3O7 is 0 - 0.047 mol / L.

5. The manufacturing method according to claim 3, wherein In step (1), the stirring time is 0.5 - 0.6 h, the aging time is 11.5 - 12.5 h, the aging temperature is room temperature, the washing and centrifugation speed is 8000 - 9000 r / min, the drying time is 7.5 - 8.5 h, and the drying temperature is 55 - 65 °C.

6. The manufacturing method according to claim 3, characterized in that, In step (2), the Zn source, In source and S source are ZnCl2, InCl3·4H2O and thioacetamide TAA respectively, and the mass ratio is 9 - 10:4 - 5:5 - 6.

7. The manufacturing method according to claim 3, characterized in that, In step (2), the concentration of ZnCl2 is 0.004 - 0.006 mol / L, the concentration of InCl3·4H2O is 0.004 - 0.006 mol / L, and the concentration of TAA is 0.009 - 0.011 mol / L.

8. The manufacturing method according to claim 3, characterized in that, In step (2), the volume ratio of water to glycerol is 14 - 15:3 - 4.

9. The manufacturing method according to claim 3, characterized in that, In step (2), the stirring time is 0.5 - 0.6 h, for the hydrothermal reaction, the heat preservation temperature is 75 - 85 °C, the heat preservation time is 1.5 - 2.5 h, and the washing and centrifugation speed is 8000 - 9000 r / min.

10. Application of the nickel-cobalt Prussian blue-ZnIn2S4 core-shell photocatalyst described in claim 1 in highly efficient hydrogen production by photocatalytic water splitting.